2021
DOI: 10.3390/microorganisms9061332
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic Reconstruction and Metabolic Potential of the Genus Aminobacter

Abstract: Bacteria belonging to the genus Aminobacter are metabolically versatile organisms thriving in both natural and anthropized terrestrial environments. To date, the taxonomy of this genus is poorly defined due to the unavailability of the genomic sequence of A. anthyllidis LMG 26462T and the presence of unclassified Aminobacter strains. Here, we determined the genome sequence of A. anthyllidis LMG 26462T and performed phylogenomic, average nucleotide identity and digital DNA-DNA hybridization analyses of 17 membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Nitrogen availability is often a growth-limiting factor for bacteria, and strains of Aminobacter are known for their versatile abilities to utilize nitrogenous compounds, thereby conferring them a selective advantage in the environment. , Here, we tested the growth of strain NyZ550 on various nitrogenous compounds (2 mM) analogous to MET or derived from MET. The results showed that strain NyZ550 was able to use trimethylamine, DMA, methylamine, and 1-methylbiguanide as sole carbon, nitrogen, and energy sources for its growth (Figures A and S2).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Nitrogen availability is often a growth-limiting factor for bacteria, and strains of Aminobacter are known for their versatile abilities to utilize nitrogenous compounds, thereby conferring them a selective advantage in the environment. , Here, we tested the growth of strain NyZ550 on various nitrogenous compounds (2 mM) analogous to MET or derived from MET. The results showed that strain NyZ550 was able to use trimethylamine, DMA, methylamine, and 1-methylbiguanide as sole carbon, nitrogen, and energy sources for its growth (Figures A and S2).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Under aerobic conditions, dimethylamine could not be identified (<0.02 mM). Dimethylamine is reported to be oxidized by a monooxygenase in other Aminobacter strains (Artuso et al, 2021) and this could explain the failure to detect it here. In an effort to trap dimethylamine if it were formed, resting cell suspensions were incubated with metformin under anaerobic conditions and then combined with a derivatizing reagent (FMOC-Cl).…”
Section: Identification and Metabolic Characterization Of Aminobacter...mentioning
confidence: 74%
“…Both glyphosate degradation pathways: the sarcosine pathway through the production of the enzyme C-P lyase and the AMPA pathway through the production of the enzyme GOX were potentially induced during the experiment. Indeed, some members of the genera Streptomyces, Bacillus and Pseudomonas are known to use both pathways to degrade glyphosate (Singh et al, 2019(Singh et al, , 2020, while Geobacillus uses the AMPA pathway (Obojska et al, 2002) and Lysinibacillus and Aminobacter use the sarcosine pathway (Artuso et al, 2021;Gonz alez-Valenzuela & Duss an, 2018). Furthermore, glyphosate degradation is thought to be activated in Aminobacter, Lysinibacillus, Geobacillus, Pseudomonas and Bacillus to obtain inorganic phosphorus molecules, while Streptomyces uses it as a source of both phosphorus and nitrogen.…”
Section: Community Profilementioning
confidence: 99%